Beer advertising and national identity: drinking who we are - Zantides, Evripides (My University, 2015)
National identity is not just a notion based on people sharing common history, cultural tradition, language, religion or land, but also as Edensor (2002) suggests, is a result of characteristics and behaviors that take place in everyday practices, rooted in the mundane and the verbal/non-verbal vernacular language of people. From a similar perspective, Anderson (1997) identifies the standard interpretations of nationalism and looks among other, at features of culture like language and the invention of printing in the middle of the 15th century, as means of constructing “imaginedcommunities” for people who share a national affiliation. With the evolution of printing methods, technology and the growth of Graphic and Visual Communication in a wider sense, print or screen Advertising became a field of major cultural influence. From the construction of gender stereotypes (Goffman), family, aesthetic and social values (Barthes, Bertin, Beasley & Danesi) to national identity it suggests “who we are” and what “we do as people” through a variety of representations in national advertisements of products or social services. The purpose of this study is to examine through a semiotic analysis (Barthes, Bertin, Eco) the verbal and non-verbal messages of a series of KEO Beer advertisements since Cyprus declared state independence in 1960 until today, as examples of extracting messages that deal with national identity ideologies. KEO Beer is a local national manufacturer of beer founded in 1927 and is known to be the largest and most prestigious beverage supplier on the island of Cyprus. The advertisements were drawn from the Press and Information Office (PIO) in Cyprus, the archives of different newspapers and magazines and from various advertising agencies that have dealt with this client.
Keywords: Beer; Advertisements